Affiliated Common Value Auctions with Costly Entry - Murto, Pauli; Välimäki, Juuso (Review of Economic Studies, 2025)
Abstract Many auctions and procurement contests entail non-trivial bidding costs, which makes the bidders’ participation decisions endogenous to the auction design. We analyse the effect of different auction rules on potential bidders’ incentives to participate. We focus on first-price auctions with affiliated common values and a large pool of potential bidders. Our main interest is on auctions where the realized number of bidders is unknown at the bidding stage. In contrast to the standard case, both participation and bidding decisions are often non-monotonic in the symmetric equilibrium of our model. The expected revenue to the seller is often higher in the auction where the realized number of participating bidders is not disclosed.